THE ISLAND IMAGE AND GLOBAL LINKS IN PUERTO RICAN CINEMA OF THE 21ST CENTURY (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
This essay looks back at the production of Puerto Rican films in the 1980s and 1990s as the point of departure for young Puerto Rican filmmakers in the first decades of the 21st century. Even as the stories of this newer generation differ, their concern with the island image and diasporic movement continue to question Puerto Rican identity. Problems of local film production and outside distribution remain for each film project. This essay analyzes a number of key films by a diverse group of directors whose goal is to rethink the concept of a Puerto Rican cinema.